Effect of instability resistance training on core muscle strength among athletes: a systematic review - Gao, Jianxin; Abdullah, Borhannudin; Omar Dev, Roxana Dev (Horizon Research Publishing, 2024)
Background: Although instability resistance training (IRT) frequently engages as a form of muscle training, little has been reported in the literature about the effect of IRT on core muscle strength. Objectives: This study aims to conduct a systematic review of the impact of IRT on core muscle strength among athletes. Design: This study used the (PRISMA) guidelines and databases such as Web of Science, EBSCOhost (SPORTDiscus), PubMed, and Scopus for the original reference collection. This article collected 149 articles, and only 8 met the analysis criteria. Result: Each article’s quality was determined using the PEDro scale, the scoring for 8 articles ranged from 7-9 with a low risk of bias. IRT could significantly improve isometric, isotonic, and isokinetic core muscle strength among Judo athletes, adolescent elite athletes, volleyball players, soccer players, collegiate athletes, and rhythmic gymnasts using unstable surfaces or environments (i.e., Suspension trainer, Swiss ball, Sissel pillows, Indo board with flow cushion, Stability ball, Airex balance pad, Togu power ball, Thera-Band, BOSU ball, Balance disc and so on). Conclusion: Theoretically, this study indicated that IRT is an improvement training method for activating core muscles, enhancing coordination between agonistic and antagonistic muscles, and improving muscle proprioception. In addition, based on emphasizing the integration of other training actions, IRT adopts an unstable form closer to specialized exercises or increasing difficulty to improve training efficiency and effectiveness. Practice has shown that continuous IRT has a positive promoting effect on core muscle strength than traditional training methods. Therefore, this review suggests that IRT should be considered in athletes’ daily training routines for core muscle strength. © 2024 by authors, all rights reserved.